Employability program for domestic violence victims living in long-term shelters - Charro, Maria Inês Gonçalves (2018)
Domestic violence (DV) is a globalized problem with particularly relevant proportions in Portugal, where victims suffer numerous consequences from this trauma, including a high unemployment rate upon their stay in long-term shelters. The present thesis is integrated in the SIB Research Program from Maze, and evaluates the feasibility of using a social impact bond mechanism to finance employability training for DV victims that includes English classes and a 14-weeks Bootcamp for coding. The main findings from this study result from a value-for-money case and suggest that a social impact bond is a suitable funding mechanism to finance this new intervention model.